Pengaruh Green Marketing Mix Terhadap Kepuasan Wisatawan Pada Destinasi Wisata Hiu Paus Desa Botubarani Kabupaten Bone Bolango Provinsi Gorontalo - Rahman, Endi; Asnawi, Melan Angriani; Sau, Muhamad Fajrin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the extent to which the Green Marketing Mix influences tourist satisfaction at the Whale Shark tourism destination in Botubarani Village, Bone Bolango Regency, Gorontalo Province. The sampling technique employed was Non-Probability Sampling, with a total of 120 respondents determined using the Malhotra formula. Data were collected through a questionnaire distributed to domestic tourists visiting the Whale Shark tourism destination in Botubarani Village. The analytical tool utilized was multiple linear regression, with data analyzed using SPSS version 30. The results of the multiple linear regression analysis show that the Green Marketing Mix variable positively and significantly influences tourist satisfaction by 75,5%. This indicates that the better the implementation of the green marketing mix, the higher the level of tourist satisfaction.